Efficacy of Probiotic Lozenges in Reducing Periodontal Pathogens in High-Risk Populations - Bushra Adeel, Muhammad Amjad Bari, Maha Maqbool, Irshad Ahmed, Sadaf Raffi, Muhammad Sami Iqbal (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Elevated colonization by periodontal pathogens such as Porphyromonas gingivalis andAggregatibacter actinomycetemcomitans contributes to chronic periodontal disease and systemichealth risks. This double-blind, randomized, placebo-controlled trial evaluated the impact of dailyprobiotic lozenges containing Lactobacillus reuteri DSM 17938 and ATCC PTA 5289 on